Professor Barry Fraser's Contributions to Science Education Research - Aldridge, Jill (Springer, 2011)
In this article, I endeavour to convey the depth of Barry Fraser’s contributions to science education research, including his tireless endeavours to promote and advance research, especially the field of learning environments, the realisation of his vision to create one of the largest doctoral programs in science and mathematics education in the world, his leadership capacity in terms of guiding and leading an internationally renowned centre and large-scale cross-national and cross-cultural studies, his dedication towards human capacity building in Africa, Asia and elsewhere, his capacity as a mentor and editor that have seen the publication of numerous journal articles and books and the ongoing success of science education research journals.